Long-term exposure to low-level ambient BTEX and site-specific cancer risk: A national cohort study in the UK Biobank - Kexin Yu; Ying Xiong; Renjie Chen; Jing Cai; Yaoxian Huang; Haidong Kan (Eco-Environment & Health)
Benzene, toluene, ethylbenzene, and xylene (BTEX) have been associated with certain cancers in the occupational population. This study aimed to investigate the associations between low-level ambient BTEX exposure and cancer risks in the general population. We leveraged data from the UK Biobank and included individuals free of cancer at 2006–2010 baseline. Annual concentrations of BTEX were estimated using a chemistry-climate model, and the associations between BTEX and incident overall and 18 site-specific cancers were investigated with Cox proportional hazard models. We also fitted restricted cubic splines to explore the exposure-response relationships. The study sample comprised 409,579 participants [mean age 56.2 (8.11) years; 219,315 (53.5%) females]. Over a mean (SD) follow-up period of 11.2 (2.64) years (4,597,164 person-years), 60,777 overall incident cancer cases occurred. The results showed significant associations between overall cancers and benzene [HR 1.93 (95% CI: 1.89, 1.96)], toluene [1.25 (1.23, 1.26)] and xylene [1.11 (1.10, 1.12)]. Benzene and toluene were associated with a higher risk of 18 site-specific cancers. For xylenes (a summation of ethylbenzene, m/p-xylene, and o-xylene in the model), significant associations with multiple myeloma, hepatobiliary tract, thyroid, or connective soft tissue were not observed. Exposure-response curves suggested a higher risk of overall cancer beyond the benzene threshold. For toluene and xylene, there was no threshold or plateau across the range of exposures. This large-scale prospective cohort study demonstrates that long-term exposure to low-level ambient BTEX could increase the risk of overall and site-specific cancers in the general population.